EFFECTIVENESS ANALYSIS OF THERMALLY AND STEAM ACTIVATED PLUM SEED ADSORBENTS - Usmonova, Zulfiya (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article describes the results of the activation of plum pit waste using temperature and water vapor, as well as the analysis of the composition of wastewater based on a selected sample. These adsorbents are intended for the treatment of wastewater from industrial enterprises. The research methods were carried out based on samples presented in the literature and GOST standard indicators. According to the results, the carbon sample pyrolyzed at 500 0C and steam activated at 800 0C demonstrated high adsorption properties and efficiency.In conclusion, it can be said that the release of O2 and Si elements from the grain composition after thermal pyrolysis and steam treatment leads to an increase in the C number of the obtained activated carbon and an increase in its adsorption properties.